2007
DOI: 10.1002/bip.20888
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the intrinsic flexibility of the SL1 stem‐loop from genomic RNA of HIV‐1 as probed by molecular dynamics simulation

Abstract: The SL1 stem-loop is the dimerization initiation site for linking the two copies of the RNA forming the HIV-1 genome. The 26 nucleotides stem contains a defect consisting on a highly conserved G-rich 1-3 asymmetrical internal loop, which is a major site for nucleocapsid protein binding. Several NMR attempts were undertaken to determine the internal loop structure in the SL1 monomer. However, the RNA constructs used in the different studies were largely mutated, in particular with replacement of the nine nucleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…X-ray and NMR studies of RNAs can be complemented by molecular dynamics (MD), which provides dynamic data and additional insight into the structure. For instance, MD simulations can characterize isolated RNA building blocks independent of their structural context. The simulations capture intrinsic stochastic fluctuations of geometries and reveal intrinsic elastic properties that are important for function. In addition, simulations can disclose whether an RNA building block is entirely internally relaxed or is deformed due to its interactions with the surroundings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…X-ray and NMR studies of RNAs can be complemented by molecular dynamics (MD), which provides dynamic data and additional insight into the structure. For instance, MD simulations can characterize isolated RNA building blocks independent of their structural context. The simulations capture intrinsic stochastic fluctuations of geometries and reveal intrinsic elastic properties that are important for function. In addition, simulations can disclose whether an RNA building block is entirely internally relaxed or is deformed due to its interactions with the surroundings.…”
Section: Introductionmentioning
confidence: 99%
“…13 X-ray and NMR studies of RNAs can be complemented by molecular dynamics (MD), which provides dynamic data and additional insight into the structure. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] For instance, MD simulations can characterize isolated RNA building blocks independent of their structural context. The simulations capture intrinsic stochastic fluctuations of geometries and reveal intrinsic elastic properties that are important for function.…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies have covered longer timescales with stable simulations of solvated and neutralized systems. [37][38][39][40][41][42][43] Comparative studies of duplex RNA and DNA have revealed a striking contrast in structural flexibility. 44,45 Attention has been focused both through experiment and simulation 46 on the phenomenon of base pair opening and closing, which has been found to occur much more readily in RNA than in DNA.…”
Section: Introductionmentioning
confidence: 99%